The impact of substance abuse on learners from dysfunctional families at Ipelegeng Location in Schweizer-Reneke - Masilo, Daniel Tuelo (University of Limpopo (Turfloop Campus), 2012)
Refer to document
Thesis (M.A. (Social Work)) -- University of Limpopo, 2012
Keywords: Substance abuse; Learners; Dysfunctional families; 362.29; Substance abuse -- South Africa; Dysfunctional families -- South Africa; High school students -- South Africa -- Conduct of life